Determination of abamectin in citrus fruits using SPE combined with dispersive liquid–liquid microextraction and HPLC–UV detection. Issue 16 (13th August 2013) - Rezaee, Mohammad; Mashayekhi, Hossein Ali; Saleh, Abolfazl; Abdollahzadeh, Yaser; Naeeni, Mohammad Hosein; Fattahi, Nazir
<x xml:space="preserve">Abstract</x> A new pretreatment method, SPE combined with dispersive liquid–liquid microextraction, was proposed for the determination of abamectin in citrus fruit samples for the first time. In this method, fruit samples were extracted by ultrasound‐assisted extraction followed by SPE. Then, the SPE was used as a disperser solvent in the next dispersive liquid–liquid microextraction step for further purification and enrichment of abamectin. The effects of various parameters on the extraction efficiency of the proposed method were investigated and optimized. Good linearity of abamectin was obtained from 0.005 to 10.0 mg/kg for B1a and from 0.05 to 10.0 mg/kg for B1b with correlation coefficient (r2) of 0.998 for B1a and 0.991 for B1b, respectively. The LODs were 0.001 and 0.008 mg/kg (S/N = 3) for B1a and B1b, respectively. The relative recoveries at three spiked levels were ranged from 87 to 96% with the RSD less than 11% (n = 3). The method has been successfully applied to the determination of abamectin in citrus fruit samples.